Unveiling the Formation of Political Identities of the Filipino Youth in Tacurong City, The Philippines - Daanoy, Lynsey Faye D.; Cruz, Eau Haiana D. Dela; Hitalia, Paul Asi C.; Sumpo, Wendelyn Joyce P.; Besa, Adonis S. (Indonesian Journal of Teaching in Science, 2021)
The purpose of this study was to investigate the Filipino youth’s participation in politics regarding how their political identities were formed. The novelties in this study are (1) political identities of the Filipino youth, and (2) factors affecting the political identity formation of the Filipino youth. A qualitative case study approach was used to analyze the different statements of the Filipino youth towards the factors that made them be involved in politics, their political identities, and their political identity. Six Filipino youths residing in Tacurong City participants were purposively chosen and interviewed via Google Meet due to COVID-19 restrictions. As revealed by the data gathered, issues in the society, the availability of information to the public, their relationship circle, and their respective school’s Influence was found to play an essential role in making the Filipino youth participate in politics. The same factors such as the issues in the society, availability of information to the public, relationship circle, and the influence of school were also responsible for the formation of their current political identity. It is concluded that the Filipino youth’s political participation and identity were the results of the significant influence of the society. This study has a major impact in contributing to the knowledge on how the youth behave and why they have different perspectives and preferences of sides specifically in politics.